Karyological study on Turkish Endemic Fritillaria baskilensis Behçet. (Liliaceae) - Kıran, Yaşar; Gedik, Osman (My University, 2014)
Endemic Fritillaria baskilensis Behçet., which is found only in one locality of Elazığ-Baskil province (Selil mountain) in East Anatolia, was karyologically examined. Chromosome numbers of Fritillaria baskilensis were determined as 2n=24. It was observed that chromosomes of the species examined had median region (m), submedian region (sm), subterminally (st), terminal region (t) and terminal point (T) centromeres. Haploid karyotype formula is 2 m + 2 sm + 3 st + 1 t + 4 T. Metaphase chromosome length ranged from 9.17 to 18.76 ?m and the total haploid chromosome length was 146. 55 ?m. Karyotype analysis of Fritillaria baskilensis species has been conducted for the first time by us.

Doğu Anadolu’ da yer alan Elazığ’ ın Baskil ilçesinde sadece bir lokalitede (Şelil dağı) bulunan endemik Fritillaria baskilensis Behçet., karyolojik olarak incelendi. Kromozom sayısı 2n=24 olarak belirlendi. İncelenen türün kromozomlarının median bölgeli (m), submedian bölgeli (sm), subterminal (st), terminal bölgeli (t) ve terminal noktalı (T) sentromerli olduğu görüldü. Haploid karyotip formülü 2 m + 2 sm + 3 st + 1 t + 4 T dir. Metafaz kromozomlarının boy uzunluğu 9.17 ?m ile 18.76 ?m arasında değişmekte ve toplam haploid kromozom boyu ise 146. 55 ?m dir. Fritillaria baskilensis türünün karyotip analizleri ilk olarak tarafımızdan yapıldı.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Chromosome number; Fritillaria; Karyotype; Liliaceae; Turkey; Türkiye; Karyotip